REPRESENTASI SEMANGAT BERBAGI EKOFEMINISME MELALUI BATIK TULIS - Demartoto, Argyo (UIN Sunan Kudus, 2017)
The objective of research was to explore the attempt the women producing batik tulis using natural colorant as the manifestation of environment care. This study was a qualitative research using explorative method taken place in Kampung Batik Laweyan and Kauman, Surakarta. The result of research showed that the emergence of stamping and printing batik led the batik tulis (written batik) to be marginalized. Many batik entrepreneurs shifted to them and only few survived with batik tulis production. The opportunity of working and applying the female batik laborers’ skill reduced. The production of stamping and printing batik using artificial colorant affected adversely the environment with its waste as the form of injustice as it contaminated the environment and marginalized the women. The spirit of ecofeminism sharing through batik tulis creation with natural colorant was the women’s attempt of working and contributing to conserve the environment. This social movement is the manifestation of women’s care about the living environment sustainability, conveying self-controlling values and controlling the passion of dominating amid industrialization, and the manifestation of sustainable development and ethical business.